2016
DOI: 10.1155/2016/7273801
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Ectopic Liver on Gallbladder Serosa with a Brief Review of the Literature

Abstract: This case describes an intraoperative incidental finding and surgical removal of ectopic liver tissue attached to the gallbladder during a standard laparoscopic cholecystectomy for acute cholecystitis. These anomalies are rare, with interesting associations and possible clinically relevant complications. The details of the case, along with a brief literature review of embryology, common ectopic sites, and associations/complications, are presented in this paper. Since laparoscopic cholecystectomy is a very comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…One of the most important reasons for this misinterpretation is that the article is written in Japanese. Another reason is that the authors copy each other directly without carefully reading the authors’ results[ 2 , 3 , 5 , 12 , 17 , 23 , 26 , 28 , 29 , 35 , 36 , 59 , 62 ]. In the review by Yamashita and colleagues[ 78 ], 70 cases of ectopic liver were reported in the literature up to 1985.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important reasons for this misinterpretation is that the article is written in Japanese. Another reason is that the authors copy each other directly without carefully reading the authors’ results[ 2 , 3 , 5 , 12 , 17 , 23 , 26 , 28 , 29 , 35 , 36 , 59 , 62 ]. In the review by Yamashita and colleagues[ 78 ], 70 cases of ectopic liver were reported in the literature up to 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Various theories have been presented to explain the development of EL at different sites including the presence of liver cell remnants around the abdominal organs during embryonic development, the formation of liver cell buds into the chest or diaphragm during the closure of the abdomen, the formation of an EL during the process of embryonic development, or atrophy leading to a loss of connection with the liver to become a heterotopic liver. [8,9] EL can develop at various sites, such as the abdominal cavity, retroperitoneal cavity, pleural cavity, mediastinum, lungs, and heart. [2,1015] Herein, we discuss an extremely rare presentation of an EL nodule localized in the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, ELT in the gall bladder derives its blood supply either from the vascular pedicle arising with or without its own vein from the liver parenchyma or from branches of the cystic artery and sometimes through vascular structures embedded within the mesentery lying adjacent to the liver parenchyma [3]. Surgically, it becomes important to delineate the blood supply because, often, the operating surgeon might encounter uncontrollable bleeding if the blood supply has been derived from liver parenchyma itself [5]. Complications that can be associated with ectopic liver are torsion, bleeding into the peritoneum, cirrhosis, and sometimes leading to malignant degeneration to hepatocellular carcinoma due to metabolic inactivity owing to less efficient vascular and biliary ductal systems, which sometimes might be confused for occult metastases from a primary hepatoma [1,[6][7].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Arakawa et al has shown that one out of 42 ELT in the gall bladder was diagnosed as malignant [8]. Congenital anomalies like omphalocele, caudate lobe agenesis, biliary atresia, and bile duct cysts have been showed to have an association with ectopic liver [5].…”
Section: Discussionmentioning
confidence: 99%